Forms of Politeness in The Official-Business Style of The Korean Language - Nasullaeva Dilnoza Bakhodirovna (Frontline Social Sciences and History Journal, 2026)
This article examines the forms and functions of politeness in the official-business style of the Korean language, with particular emphasis on the addressive category (상대경어법). Politeness is analyzed as both a linguistic and socio-cultural phenomenon that regulates communication and reflects hierarchical relationships in Korean society. The study explores grammatical and lexical means of expressing politeness, focusing on the highest formal speech level (하십시오체) and its usage in official discourse. Through the analysis of speeches delivered by Presidents Moon Jae-in and Yoon Suk-yeol, the research highlights the role of sentence-ending forms, honorific suffixes such as –님, and forms of address in constructing respectful communication. The findings demonstrate that politeness in Korean official-business communication is deeply rooted in Confucian values and continues to evolve alongside social changes. The article concludes that politeness strategies in Korean are not only grammatical tools but also essential mechanisms for maintaining social harmony, regulating interpersonal relations, and shaping professional discourse.